MENINGKATKAN PERILAKU MORAL MELALUI METODE BERCERITA MENGGUNAKAN BIG BOOK PADA ANAK USIA 4-5 TAHUN DI KB KASIH BUNDA DESA KEMANG INDAH KECAMATAN TAMBANG KABUPATEN KAMPAR - Halimah Halimah; Zulirfan Zulirfan; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase in moral behavior in children aged 4-5 years through storytelling using the big book In Play Group Kasih Bunda Kemang Indah Village Tambang District Kampar Regency. This study is je nis studies using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are children aged 4-5 years are numbered 13 children in Play Group Kasih Bunda. The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. The research shows that using a big book story-telling method can improve moral behavior in children aged 4-5 years. It can be seen from the increase in the average percentage of behavior children in the first cycle of 62.34% which is the criterion developing according to expectations (BSH) and an increase of 33.68% in the second cycle to 83.33% who are very good at developing criteria (BSB). So, the story-telling method using a big book can improve the behavior of children aged 4-5 years in Play Group Kasih Bunda Kemang Indah Village Tambang District Kampar RegencyKeywords : Moral behavior, Storytelling Method, Big Book